Agriculture in Nicaragua : promoting competitiveness and stimulating broad-based growth. - World Bank. (Washington, DC : World Bank, 2003)
This study takes stock of major developments in Nicaragua's agricultural sector and argues that broad-based growth can be promoted by strengthening agricultural competitiveness.
Includes bibliographical references (p. 57-61).
oif 11/08/15
Loan
Keywords: Agriculture -- Economic aspects -- Nicaragua